2010
DOI: 10.1002/app.32992
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene rubber filled with silica generated in situ

Abstract: We modified synthetic isoprene rubber by means of the in situ generation of silica particles through the sol-gel process starting from tetraethoxysilane (TEOS) as an inorganic oxide precursor. Different reaction conditions were investigated with variations in the initial TEOS content, the reaction time of the sol-gel process, and the presence of a coupling/surfactant agent (octyltriethoxysilane). Organic-inorganic hybrid materials with a silica content up to 70 phr were obtained with the complete conversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…In this study, we investigated the preparation and characterization of EPDM filled with in situ‐generated silica nanoparticles. Our approach is similar to the investigations of Messori et al on the in situ generation of silica from TEOS into isoprene and EPDM rubbers with in situ‐generated silica. In this investigation, the reaction time of preparation was increased in order to improve the mechanical, thermomechanical, and thermal properties of the EPDM matrix.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this study, we investigated the preparation and characterization of EPDM filled with in situ‐generated silica nanoparticles. Our approach is similar to the investigations of Messori et al on the in situ generation of silica from TEOS into isoprene and EPDM rubbers with in situ‐generated silica. In this investigation, the reaction time of preparation was increased in order to improve the mechanical, thermomechanical, and thermal properties of the EPDM matrix.…”
Section: Introductionmentioning
confidence: 74%
“…The glass transition temperature ( T g ) decreased by 1–4°C for the silica‐containing samples (Table ), which is in agreement with the equilibrium swelling and gel content results, that indicated a decrease in the crosslinking density of the vulcanized rubber. Further explanations of this behavior was suggested by Messori et al , who investigated IR/SiO 2 composites generated through in situ synthesis, and by Ikeda et al [22], who investigated styrene‐butadiene rubber filled composites generated through in situ synthesis. Messori suggested that the decrease is due to the higher mobility of the polymer chains due to larger free volume caused by the presence of nonadhering nano‐objects inside the polymer bulk, while Ikeda suggested that the rubber may have been plasticized by residual oligomers from the sol–gel reaction.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have functional groups suitable for improving filler-matrix interactions, thus allowing for a better silica dispersion and a higher mechanical reinforcement. 4 Messori et al recently published several papers on the in situ generation of silica from TEOS into isoprene rubber, [13][14][15] in particular reporting detailed studies of the interrelation between preparation conditions, structure and mechanical reinforcement. A similar approach was used in the present study on the preparation and characterization of ethylene-propylene-diene-monomer (EPDM) rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports are available in the literature on the in situ generation of silica in the different rubber matrices such as natural rubber (NR), isoprene rubber (IR), styrene butadiene rubber (SBR), polydimethylsiloxane (PDMS), ethylene propylene diene monomer rubber (EPDM), butadiene rubber (BR), acrylic rubber (ACM), and chloroprene rubber (CR) . However, research on nitrile rubber (NBR) filled with in situ silica is very limited.…”
Section: Introductionmentioning
confidence: 99%